The Factors That Influence the Efficiency of Construction Management in State-Controlled Universities - นพวงศ์ ณ อยุธยา, พิชามญชุ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study employed a survey research design with the objectives of examining the factors affecting the efficiency of construction management in autonomous public universities and developing guidelines to improve construction management processes for greater effectiveness. The sample consisted of 336 internal personnel from autonomous public universities, including procurement inspection committee members, project supervisors, and procurement officers. The research instrument was a five-point Likert scale questionnaire. Data were analyzed using percentage, mean, and standard deviation. The findings revealed that, overall, respondents demonstrated a high level of perception regarding responsibility and effectiveness in performing construction management duties, both at the aggregate level and across individual institutions. The highest-rated dimensions included engineering knowledge and understanding, attentiveness and thoroughness in job performance, and workload management. The most critical practices identified were: (1) comprehensive review of construction contracts, drawings, specifications, and related requirements prior to project commencement; (2) detailed verification of acceptable tolerances and essential items; and (3) thorough inspection of the construction site to ensure compliance with approved drawings before initiating operations. In addition, factors influencing construction project performance-particularly operational and personnel-related factors-were found to have a high level of impact. Operational factors were categorized into six dimensions, ranked in descending order of importance: financial management, overall management, materials, project physical characteristics, labor skills and machinery, and documentation and contract administration. Key recommendations include that universities should establish and maintain up-to-date standard cost databases, systematically analyze budgetary risks, and conduct comprehensive site investigations prior to final design approval. These measures would help minimize scope changes, project delays, and delays in budget disbursement.